Legal Protection for Children Involved in Narctics Abuse from An Islamic Law Perspective - Yusril Aulia Patra; M. Junaidi (Universitas Muhammadiyah Surakarta, 2025)
The abuse of narcotics by children is a serious issue that threatens not only their health but also violates existing legal norms. This research focuses on the fact that children involved in such cases require an approach that is not solely punitive (repressive), but also rehabilitative. In Islamic teachings, protection of children is based on the values of compassion (rahmah), justice (al-'adalah), and public benefit (maslahah). This study explores how these principles are applied to protect children from the harmful effects of narcotics while also offering them opportunities for rehabilitation. The method used in this research is normative juridical, using a literature review approach. The legal basis used includes primary and secondary legal sources, which are analyzed deductively. The results of the analysis indicate that both Islamic law and national law align in promoting restorative justice, aiming for comprehensive protection of children. These findings are expected to serve as a foundation for developing more humane legal strategies focused on safeguarding children's rights.